Saving Lives and Limiting the Means and Methods of Warfare: Five Indonesian Tafsīr Views - Ulya Fikriyati; Ah. Fawaid (Al-Jami'ah: Journal of Islamic Studies, 2022)
Protection of non-combatants and restrictions on methods of warfare are two essential aspects of jus in bello. Dawoody’s and Hashmi’s theory states that the classical Islamic scientific tradition discusses jus in bello much more than contemporary Islamic studies do. Contemporary studies are more preoccupied with deciphering jus ad bellum as a response to the West’s stigma against Islam. This article examines the theory in the realm of Qur’anic interpretation (tafsīr). Five authoritative Indonesian tafsīrs will be the samples; Tarjumān al-Mustafīd, Marāḥ Labīd, Al-Azhar, Al-Miṣbāḥ, and Firdaws al-Naʻīm. The first two tafsīrs represent the classical era, the third came from the transitional era, and the last two tafsīrs originated from the contemporary era. The article examines the shifting trend through two main issues in humanitarian law: protection of non-combatants, civilians, and civilian objects, and limits on the methods and means of war.[Perlindungan terhadap yang bukan kombatan dan pembatasan model perang merupakan aspek penting dalam prinsip hukum jus in bello. Teori Dawood dan Hashmi menyatakan bahwa dalam tradisi pengetahuan Islam klasik justru lebih banyak membahas jus in bello daripada studi Islam kontemporer. Studi kontemporer cenderung menceritakan jus ad bellum sebagai respon terhadap stigmatisasi barat pada islam. Artikel ini akan membahas lima tafsir Qur’an yaitu: Tarjumān al-Mustafīd, Marāḥ Labīd, Al-Azhar, Al-Miṣbāḥ, dan Firdaws al-Naʻīm. Dua yang awal mewakili masa klasik, tafsir ketiga berasal dari masa transisi dan dua yang terakhir mewakili masa kontemporer. Artikel ini juga membahas pergeseran trend kajian melalui dua isu penting yaitu perlindungan pada non kombatan, sipil dan objek sipil dan pembatasan pada metode dan peralatan perang].